Peran Badan Permusyawaratan Desa dalam Mewujudkan Pembentukan Peraturan Desa yang Partisipatif di Kabupaten Pohuwato - Muslimah Muslimah (Journal on Education, 2023)
This study aims to determine the Village Consultative Body (BPD) in drafting participatory village regulations in Pohuwato District. This is a normative and empirical research approach to literary studies, statutory approaches, case approaches and historical approaches. Data collected by literary study. The results of the research show that the role of the Village Consultative Body (BPD) and the drafting of village regulations have been carried out in a participatory way but not optimal due to several factors. Village regulations must be drawn up by the BPD, but village regulations are initiated and designed by the village head. The BPD lacks knowledge related to their duties and functions in village laws, mechanisms and processes for making participatory village regulations, and the BPD is not optimal in creating synergy with the community regarding participatory village regulation making. The rights of the community in Palopo Village have been participatory in making village regulations but not optimal as stipulated in Article 96 of Law Number 12 of 2011 concerning laws relating to public participation rights. The making of the Palopo village regulations insofar as it is carried out with the village of public consultation by community leaders as community representatives from each sub-village to convey the aspirations of the community in making village regulations in Palopo Village.